Crystal structures of dichloromethane solvate and ethanol solvate of 1-chloromethyl-1,4,7-trimethyl-triazonan-1-ium chloride, (C10H23N3Cl)Cl · CH2Cl2, (C10H23N3Cl)Cl · C2H5OH - Ernst R. D.; Harvey B. G.; Oteri O. J.; Arif A. M. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
C11H25Cl4N3, C2cb (no. 41), a = 9.4241(3) Å, b = 26.115(2) Å, c = 13.5769(9) Å, V = 3341.4 Å3, Z = 8, Rgt(F) = 0.066, wRref(F2) = 0.169, T = 150 K.